A completely polyherbal conditioning and antioxidant shampoo: A phytochemical study and pharmaceutical evaluation - Riham O Bakr; Reham I Amer; Marwa A A Fayed; Tamer I M Ragab (Wolters Kluwer Medknow Publications, 2019)
Aim: A recent approach in shampoo research has been to find a natural alternative for synthetic detergents that have deteriorative effects on hair follicles. This study aimed at the formulation of a completely herbal shampoo containing a natural foaming agent, in addition to having conditioning, antioxidant, and antimicrobial effects. Material and Methods: The leaves of Salix babylonica L., Ziziphus spina-christi L. (Willd), and Glycyrrhiza glabra rhizomes were extracted with 70% methanol then quantified for their phenolic and flavonoid contents using colorimetric assays that were qualitatively identified by Ultra-performance liquid chromatography (UPLC) with tandem mass spectrometry (MS-MS). The mineral content was also estimated. The radical scavenging activity was estimated using 1,1-diphenyl-2-Picrylhydrazyl (DPPH) and the half maximal inhibitory concentration (IC50) was determined. Additionally, the antimicrobial activity was tested using agar diffusion assay and compared to vancomycin and ketoconazole. Four formulations, consisting of the different plant extracts and a combination of the extracts, were prepared and evaluated for several physicochemical properties. The best formula was evaluated for its conditioning effects using scanning electron microscope and blind touch tests by asking volunteers for grading the formulations. Results and Discussion: UPLC-MS-MS analysis of S. babylonica and Z. spina-christi allowed tentative identification of 12 phytoconstituents in each. Z. spina-christi showed the highest phenolic content and a high copper, zinc, and manganese content beside the best antioxidant activity, whereas G. glabra had a high potency against Bacillus cereus and Candida albicans. The polyherbal shampoo formulation (F4) was selected as an optimized formulation because of a high foam stability after 4 min, low wetting time (2 s), surface tension reduction, and comparable results for percent solid content. F4 showed good conditioning effect and consumer contentment. Conclusion: The formulated polyherbal shampoo is chemical free, extra-nourishing shampoo with excellent conditioning, cleansing, and antimicrobial effects.